Partisipasi Masyarakat dan Keberlanjutan Program Gerak Bersemi di Griya Prima Lestari Munthe Kabupaten Kutai Timur - Wahyuni, Yayuk Tri; Manaf, Asnawi (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
The increase of population affects the amount of household waste generated by the community, increase the amount of garbage adds to the burden of government in the management of household waste. Movement Program Clean, Healthy and Independent (Motion Bersemi) is a program that is engaged in the waste which aims to reduce the amount of waste households with 3R principles, one of the pilot areas program Motion Bersemi are in Griya Prima Lestari Munthe (GPL Munthe) Sangatta East Kutai Regency. This research was conducted in order to identify the forms and levels of community participation in stages in four stages, to analyze internal and external factors affecting the level of community participation in all stages and analyze sustainability Bersemi Motion program. The method used in this research is quantitative method with the number of respondents 83 people. The study concluded the level of participation is influenced by internal and external factors which consisted of age, the status of the house, the number of in habitants of the knowledge society, the role of government, the role of community leaders, the private sector's role and the role of community groups (RKPL). Sustainability â€œGerak Bersemiâ€ program in terms of social, economic and environmental prospects to continue to be run and developed. â€œGerak Bersemiâ€ program can gradually overcome the problem of solid waste. To sustain â€œGerak Bersemiâ€ Program and increase public participation is still required the participation of government, private and community mobilization groups to motivate the public about the importance of waste management by means of 3R. To speed up the East Kutai free from garbage problems the government should immediately extend the implementation of the program throughout the territory Bersemi Motion City Sangatta.